DETERMINAN PENYEBAB PERDARAHAN ANTEPARTUM SEBAGAI PENYEBAB KEMATIAN IBU DI RSUD Prof. Dr. MARGONO SOEKARJO PURWOKERTO - Anasari, Tri (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2016)
Antepartum hemorrhage is an emergency, which happened around 3% of all births, the causes include placenta previa, placental abruption, and bleeding unclear source. Predisposing factors which may result in antepartum hemorrhage include age, parity, history Sectio Cesaria (SC) and malnutrition. Antepartum haemorrhage cases in hospitals Margono Soekarjo Purwokerto increase from the year 2013 by 10.61% to 11.96% in 2014. Objective: To analyze the relationship between age, parity, history of SC and malnutrition with the incidence of antepartum haemorrhage and analyze the most influential factor the antepartum haemorrhage. Methods: This type of survey research analytic, retrospective case control approach. The population was all pregnant women undergo antepartum haemorrhage as many as 170 people and have not experienced antepartum bleeding as much as 1251 people. The samples were 63 as the case group and 63 as control group were taken Systematic Random Sampling. Bivariate analysis used Chi-square test. RESULTS: Most of age didn’t risk as much as 75 (59.5%), parity didn’t risk as much as 70 (55.6%), didn’t have a history of Cesaria sectio 75 (59.5%) and malnutrition as many as 66 (52, 4%). There was a relationship between age, parity, history of SC and malnutrition with antepartum haemorrhage with a p-value: 0.002, 0.001, 0.006 and 0.013. Age and parity is the factor most affecting antepartum haemorrhage with odds ratio: 3.29 and 3.17. Conclusion: There was a relationship between age, parity, history of SC and malnutrition with antepartum hemorrhage, the most influential factor to the incidence of antepartum haemorrhage are age and parity. Keywords: age, parity, history of SC, malnutrition, antepartum haemorrhage